Altering the Tropism of Lentiviral Vectors through Pseudotyping - Cronin, James (2005)
The host range of retroviral vectors including lentiviral vectors can be expanded or altered by a process known as pseudotyping. Pseudotyped lentiviral vectors consist of vector particles bearing glycoproteins (GPs) derived from other enveloped viruses. Such particles possess the tropism of the virus from which the GP was derived. For example, to exploit the natural neural tropism of rabies virus, vectors designed to target the central nervous system have been pseudotyped using rabies virus-derived GPs. Among the first and still most widely used GPs for pseudotyping lentiviral vectors is the vesicular stomatitis virus GP (VSV-G), due to the very broad tropism and stability of the resulting pseudotypes. Pseudotypes involving VSV-G have become effectively the standard for evaluating the efficiency of other pseudotypes. This review samples a few of the more prominent examples from the ever-expanding list of published lentiviral pseudotypes, noting comparisons made with pseudotypes involving VSV-G in terms of titer, viral particle stability, toxicity, and host-cell specificity. Particular attention is paid to publications of successfully targeting a specific organ or cell types.